"Tell Me Who Your Enemies Are": Government Reports About the "Cult" Phenomenon in Israel. Issue 4 (December 2013) - Ruah‐Midbar, Marianna; Klin‐Oron, Adam
<x xml:space="preserve">Abstract</x> Between 1982 and 2011, four Israeli governmental reports addressing ostensible dangers from "cults" (new religious movements, or NRMs) were issued. The 1980s reports use a collectivist discourse, in which the state sees itself as defending the collective's borders from external threats and representing various sectors while seeking consensual values. The 1990s report marks an interim stage in which the state tries to balance individual liberties with sectoral interests. The 2011 report focuses solely on harm to individuals and is the harshest of the four. The reports reflect milestones in three processes of change that have taken place in Israeli society: from a collectivist‐hegemonic ethos to a multisectoral one; from a focus upon society to a focus on the individual; and from nationalistic values to universalistic ones. At every point in time, NRMs represented a different perceived threat to Israeli society. We explain how multisectoralism brings about both tolerance toward new religious phenomena and fierce anti‐cultic activity.